2019
DOI: 10.1039/c9ta08264f
|View full text |Cite
|
Sign up to set email alerts
|

Electric power generation using paper materials

Abstract: Paper materials are utilized in moist-electric power generation, and a ‘power’ book that harvests moist-electricity is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 25 publications
1
76
1
5
Order By: Relevance
“…It has been found that commercial printing paper, pure cellulose films, and filler-free filter paper have abundant polarized oxygen groups that can release free protons allowing them to be used to generate electricity in moist conditions. [95,164] These MEGs are based on the ionic diffusion gradient mechanism, but the gradient in ion concentration and the electric field readily collapse, yielding transient voltage pulses when exposed to moisture (Figure 12). It is relevant that paper incorporating power generation units can also be assembled into various shapes and structures such as books, origami, and Chinese traditional paper fans (Figure 12a), with capabilities of harvesting energy from ambient moisture.…”
Section: Biofiber-based Megs For Transient Electricity Outputmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that commercial printing paper, pure cellulose films, and filler-free filter paper have abundant polarized oxygen groups that can release free protons allowing them to be used to generate electricity in moist conditions. [95,164] These MEGs are based on the ionic diffusion gradient mechanism, but the gradient in ion concentration and the electric field readily collapse, yielding transient voltage pulses when exposed to moisture (Figure 12). It is relevant that paper incorporating power generation units can also be assembled into various shapes and structures such as books, origami, and Chinese traditional paper fans (Figure 12a), with capabilities of harvesting energy from ambient moisture.…”
Section: Biofiber-based Megs For Transient Electricity Outputmentioning
confidence: 99%
“…m) Reproduced with permission. [ 95 ] Copyright 2019, Royal Society of Chemistry. n) Reproduced with permission.…”
Section: Selection Of Materials For Harvesting Energy From Moisturementioning
confidence: 99%
See 1 more Smart Citation
“…However, the observed voltage was only microvolts/cm and the fabrication and handling of CNTs is incompatible with large-scale applications. Similarly, it has been observed that a few millivolts can be generated by using carbon black 20 , graphene oxide 27,28 , monolayer graphene 29,30 , as well as carbon-based hybrid systems grown on oxide nanowire networks 31 or cellulose-based lter paper printed with multi-walled CNTs 32,33 . However, most of these carbon-based materials adhere only weakly to substrates, making devices rather fragile and hard to scale up, and the output voltage was below 100 mV/cm 2 range at the largest 22,27,29,30,34,35 .…”
Section: Introductionmentioning
confidence: 98%
“…直到2017年, 周军和郭 万林团队 [20] . 中国科学院苏州纳米技术与纳米仿生研究所张挺研究 组 [23] [33] . 除了碳基材料, 大连理工大学边继明研究组 [34] 和 东莞理工学院高峰研究组 [25] 将Ni-Al层状氢氧化物涂 .…”
unclassified